"Dude, I'm Seventeen … It's Okay Not to Have Sex by This Age": Feelings, Reasons, Pressures, and Intentions Reported by Adolescents Who Have Not Had Sexual Intercourse. Issue 9 (21st November 2016) - Heywood, Wendy; Patrick, Kent; Pitts, Marian; Mitchell, Anne
Abstract : This study investigated feelings, reasons, pressures, and previous sexual experiences reported by students who have not had sexual intercourse and how these factors are associated with self-rated likelihood of having sex during the next year. Using data from the Fifth National Survey of Australian Secondary Students and Sexual Health ( n = 783), this study found, in general, students had positive feelings about not having sex. Reasons for not having sex such as being proud to say no and not being ready were rated higher in importance than fear of potential outcomes or religious/cultural beliefs. Students reported limited pressure from parents and friends and, despite not having sexual intercourse, more than half of the sample had experienced some form of sexual activity. Stronger likelihoods of having sex during the next year were reported by students who had previously engaged in other sexual practices, reported more pressure from friends to have sex, and had negative feelings about not having sex. Sexuality educators can use these findings to guide approaches to sex education, emphasizing feelings, intentions, and reasoning over fear tactics. Discussion of a range of sexual practices will address more closely the experiences of young students as they begin their sexual lives.